2016
DOI: 10.23907/2016.064
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting and Streamlining the Medical Record Acquisition Process in Death Investigation Systems

Abstract: Though medicolegal death investigation (MDI) systems are generally associated with criminal justice, they serve an integral role in the realm of public health and safety. Medicolegal death investigation offices collect information, including medical records, from a variety of outside sources. For data to travel efficiently, transmission should be fully integrated between the MDI office and external organizations. This is often not the case. Delays in the transmission of medical records in particular lead to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, obtaining the operative report or other records should not be any more time‐consuming than obtaining the necessary antemortem radiographs that would be required for radiographic comparison. A recent survey of ME/C offices showed that 57% of offices received requested records within 1–3 days and 46% had access to some electronic medical records . In one case in this study, a serial number was identified on a prosthetic knee joint, but the corresponding serial number could not be identified in the operative report which had been requested from an outside institution.…”
Section: Discussionmentioning
confidence: 65%
“…However, obtaining the operative report or other records should not be any more time‐consuming than obtaining the necessary antemortem radiographs that would be required for radiographic comparison. A recent survey of ME/C offices showed that 57% of offices received requested records within 1–3 days and 46% had access to some electronic medical records . In one case in this study, a serial number was identified on a prosthetic knee joint, but the corresponding serial number could not be identified in the operative report which had been requested from an outside institution.…”
Section: Discussionmentioning
confidence: 65%